Chemical composition and antimicrobial activity of Pinus halepensis from Algeria - Messaoud Ramdani; RIMA HAICHOUR1; TAKIA LOGRADA; PIERRE CHALARD; GILLES FIGUEREDO4 (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Haichour R, Lograda T, Ramdani M, Chalard P, Figueredo G. 2020. Chemical composition and antimicrobial activity of Pinus halepensis from Algeria. Biodiversitas 21: 4345-4360. The chemical composition of Pinus halepensis essential oils and their antibacterial activities were investigated. Plant samples were collected in the flowering stage from the East locality of Algeria. The aerial parts of P. halepensis obtained from fifteen localities were subjected to a hydro-distillation, providing pale yellow viscous oils. The obtained yield average was 0.64 ± 0.37%. The analysis of the chemical composition of essential oils was performed by using GC and GC / MS. A total of thirty-seven compounds representing 99.4 ± 0.5% of the total oils were identified in P. halepensis. The hydrocarbon compounds were found to dominate essential oils in P. halepensis. In addition, the major compounds were caryophyllene-E (29.06 ± 8.5%), myrcene (19.14 ± 6.67%), a-pinene (16.86 ± 3.35%), phenyl ethyl 3-methyl butanoate (5.67 ± 2.47%), a-humulene (4.81 ± 1.43%), terpinolene (3.94 ± 1.6%) and sabinene (3.11 ± 1.84%). Based on their chemical composition, essential oil samples were clustered in five groups by UPGMA analysis. The first group includes the Tafrent essential oil population. It is characterized by the phenyl ethyl-3-methyl butanoate – Sabinene ? ?3-carene chemotype. The second group was subdivided into two clusters. The first cluster or chemotype was characterized by the myrcene ? ?-pinene ? caryophyllene-E. The second chemotype was characterized by caryophyllene-E ? ?-humulene ? myrcene. The essential oil of P. halepensis is an effective antimicrobial against Staphylococcus aureus; Klebsiella pneumonia; Salmonella enteric spp arizonae; Listeria innocua; Proteus mirabilis and Bacillus cereus, and no effect on the E. coli and Pseudomonas aeruginosa.